INCIDENCE, SOCIODEMOGRAPHIC, AND CLINICAL CHARACTERISTICS OF ANOVULATORY INFERTILITY AMONG WOMEN PRESENTING TO A SECONDARY CARE HOSPITAL OF NORTH INDIA - ACHALA RAWAT; KRISHNA MUKHERRJEE; SHUBHA PANDEY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of the study was to assess the incidence and factors associated with anovulatory infertility among reproductive-age women. Methods: The study was an observational cross-sectional study conducted in the Department of Obstetrics and Gynecology of a secondary care hospital of Prayagraj, Uttar Pradesh over a period of 20 months, from October 2020 to May 2022. A consecutive sampling method was used to recruit a total of 100 women presenting with a complaint of inability to conceive even after regular intercourse over the past 1 year into the present research. Based on the detailed physical and clinical examination as well as laboratory findings, the final diagnosis of the cause and the nature of the infertility (primary/secondary) were established. Results: Among the 100 patients, 22 were found to have anovulatory infertility. The mean age was 28.68±3.71 years. Majority (50%) belonged to the upper socioeconomic class the mean weight of patients was 55.91±5.66 kg and the mean body mass index was 22.85±2.21 kg/m2. Majority presented with normal menstruation, followed by oligomenorrhoea (45.5%). 81.8% of the participants had hirsutism. The mean follicle-stimulating hormone of patients was 6.30±1.87 IU/mL, the mean luteinizing hormone was 6.04±1.83 IU/mL, mean estradiol was 45.00±6.50 pg/mL, mean anti-mullerian hormone was 6.94±2.13 ng/mL, mean total cholesterol was 76.21±16.86 ng/dL, mean thyroid stimulating hormone was 2.63±0.98 mIU/L and mean prolactin was 15.94±4.94 ng/mL. About 86.4% had primary infertility, the most common cause being polycystic ovarian syndrome (PCOS, 63.6%). This was followed by hyperprolactinemia (13.6%) and hypothyroidism (9.2%). Secondary anovulation associated with obesity was identified in 13.6% of the patients. Conclusion: The incidence of anovulatory infertility was 22%, with the majority being primary infertility due to PCOS, followed by hyperprolactinemia, and hypothyroidism.